Estabilidade termo-oxidativa de óleo mineral isolante: estudo de metodologias e otimização de aditivos - Pontes Filho, Antonio Arruda (2017)
Transformers play a key role in the production, transmission, distribution and industrial use of electric power. For their operation, they need a good insulation system, consisting of cellulose paper and insulating oil, the latter being responsible for 70-80% of the electrical insulation. The use of insulating oil is due to its dielectric and cooling properties, however, the thermo-oxidative resistance is a limiting factor for the applicability of the insulating oil. In this work, the thermo-oxidative stability of naphthenic insulating oil was studied through two accelerated oxidation methodologies: ASTM D-2440 and Modified Rancimat, with the use of antioxidant additives and commercial metal passivators. First, studies with the oxidation block (ASTM D-2440) were carried out in samples with and without additives, using a metal catalyst. Where was possible to verify the evolution of the oxidation by increasing the band 1713 cm-1 in the infrared spectrum, besides the good inhibitory action of antioxidants Irganox L115 and DBPC, from 500 mg/kg and 800 mg/kg, respectively, in set with metal passivator. The Rancimat method was modified to allow the study of oxidative stability under conditions similar to the traditional method, but maintaining the agility in obtaining the results. Thus, it was possible to determine the induction time, to evaluate the temperature variation, the strong influence of the metal catalyst, and the improved oxidative stability, only with the addition of the metal passivators (BTA or Irgamet 39) from 8 mg/kg and to study the synergy of the additives in the inhibition of oxidation. At 110 °C and 120 °C, DBPC stood at 200 mg/kg and Irganox L115 at 500 mg/kg. At 140 °C, both antioxidants, in general, obtained similar responses. For optimization of the antioxidant content and metal scavenger, a composite experimental design with replicates was performed at the central point, and the optimum concentrations were obtained for the ASTM D-2440 method, initially with the combination of Irganox L115 and Irgamer 39.